Józef Czapski - an apprenticeship of looking - Karpeles, Eric 1954- (Thames & Hudson, 2019)
This stunning monograph, a long-overdue critical appraisal of Polish artist Jozef Czapski (1896-1993), arrives at a moment when the artist's legacy is gaining new recognition. Within these pages, author Eric Karpeles conveys how making art was so enmeshed with Czapski's way of seeing and being in the world that it was second nature. Given that he lived into his 97th year, it's no surprise that the artist has works dating from every decade of the 20th century but the first. As witness to the tumultuous events of that century, he found in painting "a refuge and a salvation". Prolific as a painter, he was equally disciplined in recording the events of his life in pencil, ink, and watercolour in his journals. At a time when abstract art tended to dominate aesthetic discourse, he preferred to observe the world around him, to portray people going about their daily business. Some of his most compelling works depict theatre-goers and art lovers doing what they do best - looking
Keywords: Czapski, Józef -- 1896-1993; Czapski, Józef / 1896-1993; Bildband